DEVELOPMENT OF CMS AS A RICH INTERNET APPLICATION - Lovrekovic, Zoran (Journal of process management and new technologies, 2018)
The paper discusses the development of web CMS as a rich Internet application. In the case of the development of a real CMS, technologies for making such an application have been analyzed, as well as the methods of making a web service for communicating the client to the server side. Ways to handle the error are suggested. Alternatives to the way of querying the database were investigated. The problems were identified in the development of this RIA, and the proposed solutions were discussed. The characteristic looks of the screens of this application are shown which show a qualitative difference between the classic web application and the RIA. Appropriate recommendations that can serve as a guide to the development of such applications are given.